2019
DOI: 10.1111/idh.12417
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care provided by nurses for hospitalized patients in Korea

Abstract: Objectives To investigate registered nurses’ awareness and implementation of oral health care in patients who are hospitalized in general wards or intensive care units (ICUs) in South Korea. Methods This research was performed as a descriptive survey of 149 nurses working in nine general hospitals with at least 100 beds in major Korean cities. Results Approximately half (40.9%) of the survey respondents reported providing oral health care for hospitalized patients but that relevant protocols were not available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
0
18
0
8
Order By: Relevance
“…These groups of patients include NPO and unconscious, admitted to critical care unit and undergoing chemotherapy and radiotherapy, critically ill patients with an artificial airway. Lee et al (2019) indicated most participants considered that there is a need for evidence-based protocol for oral care for hospitalized patients, and nurses employed in the critical care unit are much more responsible in this regard compared to nurses working in the public ward [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These groups of patients include NPO and unconscious, admitted to critical care unit and undergoing chemotherapy and radiotherapy, critically ill patients with an artificial airway. Lee et al (2019) indicated most participants considered that there is a need for evidence-based protocol for oral care for hospitalized patients, and nurses employed in the critical care unit are much more responsible in this regard compared to nurses working in the public ward [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rotina de cuidados de auxiliares e técnicos de enfermagem consiste em: verificação de parâmetros vitais, preparo e administração de medicamentos, cuidados de higiene e conforto, controle de ingestão e eliminações e coleta de material para exames (Souza, Santos, & Monteiro, 2013). Em relação à rotina dos enfermeiros, a mesma é dividida em atividades gerenciais, como passagem de plantão, controle da assiduidade dos funcionários e elaboração das escalas de serviços, atividades assistenciais, como visita de enfermagem, liderança e tomada de decisão (Lee, Noh, Han, & Jeon, 2019). Porém, devido à alta demanda do serviço de saúde, enfermeiros dedicam a maior parte do tempo a atividades gerenciais.…”
Section: Discussionunclassified
“…Portanto, a falta da higiene oral favorece o aparecimento e desenvolvimento de bactérias na cavidade oral, aumentam as chances de exposição a comorbidades, como pneumonia, além de causar comprometimento do estado imunológico (Lee, Noh, Han, & Jeon, 2019). Desta forma, é possível compreender a importância da higiene oral como prática preventiva.…”
Section: Discussionunclassified
“…E para findar os exemplos, uma consequência frequente da negligência aos cuidados orais é a pneumonia nosocomial, que é obtida em uma média de 48 horas após a internação em hospital, e pode ser desenvolvida por intermédio da aspiração de agentes patológicos presentes na cavidade bucal. (Cavalcante et al, 2015;Zambrano et al, 2018;Lee et al, 2019).…”
Section: Discussionunclassified